Previous injury, sex and well-being are associated with injury profiles in 422 adolescent elite athletes of age 15-16 years: a 20-week longitudinal study - Fridén, C.; Ekenros, L.; von Rosen, P. (BMJ Open Sport & Exercise Medicine, 2023)
Background: Adolescent elite athletes have a high injury risk and many risk factors for injury have been suggested. However, there is a lack of prospective studies in adolescent elite athletes of age 15-16 years.